Acid-amide calixarene ligands for uranyl and lanthanide ions: synthesis, structure, coordination and extraction studies - Beer, P; Brindley, G; Fox, O; Grieve, A; Ogden, M; Szemes, F; Drew, M (2002)
The synthesis of a series of calix[4]arene ligands bearing lower rim 1,3-acid-amide functionality for the two-phase solvent extraction of lanthanide and uranyl ions from aqueous wastes is described. X-Ray crystal structure studies demonstrate binding of lanthanide ions at the calixarene lower rim through phenolate, carboxylate and carboxamide oxygen atoms. The crystal structures of a centrosymmetric, dimeric lanthanum(III) and non-centrosymmetric dimeric sodium(I) complexes of a 1,3-acid-dihexylamidecalix[4]arene ligand are detailed. Electrospray mass spectrometry confirms retention of this 2:2 dimeric structure for large lanthanide ions and that the smaller lanthanide ions e.g. Lu3+ form monomeric 1:1 calixarene: lanthanide complexes in solution. Extraction studies demonstrate a pH dependent uptake of lanthanide and uranyl cations by 1,3-acid-amide ligands with the nature of the carboxamide substituent largely irrelevant to extraction efficiency. Upper rim modified 1,3-dinitro and de-tert-butylcalix[4]arene ligands were prepared and NMR and ES-MS studies confirm uranyl coordination by these novel acid-amide ligands. The 1,3-dinitro and de-tert-butyl ligands exhibit superior and more efficient extraction of uranyl cations at lower pH values.